Linkages of Various Calcium Sources on Immune Performance, Diarrhea Rate, Intestinal Barrier, and Post-gut Microbial Structure and Function in Piglets - Wang, Kaijun; Yang, Anqi; Peng, Xiaomin; Lv, Feifei; Wang, Ying; Cui, Yao; Wang, Yuhan; Zhou, Jianqun; Si, Hongbin (Frontiers in Nutrition, 2022)
The purpose of this experiment was to investigate the effects of different sources of calcium on immune performance, diarrhea rate, intestinal barrier, and post-intestinal flora structure and function in weaned piglets. A total of 1000 weaned piglets were randomly assigned to five groups (10 replicate pens per treatment, 20 piglets per pen) and fed supplemented calcium carbonate, calcium citrate, multiple calcium, organic trace minerals with different concentrations of acidifier diets. The results of the study showed that the small intestine of piglets fed a diet with calcium citrate and organic trace elements had a better effect. The replacement of calcium carbonate by calcium citrate and multiple calcium had almost no significant effect on immune indexes (IL-1β, IL-6, IL-10, TNF-α) of piglets compared with the control group (p > 0.05). The five groups did not change the diarrhea rate and diarrhea index (p > 0.05). Diet of multiple calcium dramatically decreased the TP compared to the C and L diet (p < 0.05). No significant difference in HDL were noted between five groups (p > 0.05). However, the concentration of LDL in blood in multiple calcium group was significantly higher than that in group L and D (p < 0.05). Moreover, the concentration of Glu in blood in multiple calcium group was significantly higher than that in group C (p < 0.05). Compared with control group, calcium citrate plus organic trace minerals diet markedly increased UCG-005 abundance in the colon (p < 0.05). Besides, the relative abundance of Prevotellaceae_NK3B31_group had an upward trend in the colon of the M group than D group (p = 0.070). Meanwhile, calcium citrate plus organic trace minerals diet markedly increased Clostridium_sensu_stricto_1 abundance in the colon (p < 0.05). Metagenomic predictions by PICRUSt suggested that the colonic and fecal microbiota was mainly involved in carbohydrate metabolism, amino acid metabolism, energy metabolism and metabolism of cofactors and vitamins. Besides, we anticipated that different calcium would not widely alter gut and fecal microbiota function.